Clinical Implication of Systemic Immune-Inflammation Index and Prognostic Nutritional Index in Skull Base Chordoma Patients - Li, Mingxuan; Bai, Jiwei; Wang, Shuai; Zhai, Yixuan; Zhang, Shuheng; Li, Chuzhong; Du, Jiang; Zhang, Yazhuo (Frontiers in Oncology, 2021)
Inflammation associated markers and nutritional indexes are associated with survival, and act as novel prognostic grading systems in patients with cancer, though the role of these markers in chordoma remains unclear. The current study aimed to characterize systemic immune-inflammation index (SII) and prognostic nutritional index (PNI), and their relationship with clinicopathological data and survival in skull base chordoma. Our retrospective study enrolled 183 patients with primary skull base chordoma who received surgical treatment. Clinicopathological data and preoperative blood tests including neutrophil, lymphocyte, platelet counts and albumin level were collected from medical records. Neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), SII, PNI were calculated and the optimal cut-off values of these markers were used for further survival analysis via Kaplan-Meier survival analysis and Cox proportional hazards regression analysis. The value of NLR, PLR, SII and PNI in skull base chordoma ranged from 0. 44-6.48, 45.36-273.94, 113.37-1761.45 and 43.40-70.65, respectively. PNI was significantly correlated with patients' sex (p=0.005) and age (p=0.037). SII was positively correlated with NLR and PLR, but negatively correlated with PNI. The median overall survival (OS) time was 74.0 months and Kaplan-Meier survival analysis indicated that all four indexes were associated with OS. Multivariable Cox proportional hazards regression analysis identified that high SII was an independent prognostic factor for poor OS. More importantly, patients with high SII and PNI had the worst outcomes and combined use of SII and PNI increased the predictive ability for patients' survival in skull base chordoma. Our results suggest SII and PNI may be effective prognostic indicators of OS for patients with primary skull base chordoma after surgical resection. Anti-inflammatory treatment or immunotherapy may be an effective therapeutic strategy for skull base chordoma patients.